PENGARUH CURRENT RASIO (CR), RETURN ON ASSET (ROA), DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2013-2017 - Prayudita Maulita; Mujino Mujino (FE Program Studi Manajemen, 2019)
Investors before making a decision will analyze the company that is the place of investment must pay attention to several things, especially the issue of stock price information, so investors know which allocation is expected to provide additional profits. This study aims to examine the effect of current ratio, return on assets, and debt to equity ratio both simultaneously and partially on stock prices in food and beverage companies listed on the Indonesia Stock Exchange in the period 2013 to 2017. Sampling using purposive sampling method, based on predetermined criteria obtained 12 samples of food and beverage companies listed on the Indonesia Stock Exchange 2013-2017. This study uses multiple linear regression analysis with the tool used is the SPSS program. The results of simultaneous research (F test) show that the current ratio, return on assets, and debt to equity ratio are not suitable to be used to predict the stock price in food and beverage companies. Partially (T test) is generated that the variable return on assets has a positive effect on stock prices, while the current ratio variable and debt to equity ratio have no significant effect on stock prices. Keywords: Current Ratio, Return On Assets, Debt To Equity Ratio, Stock Price